Área de vida, padrão de atividade, dieta e dispersão de sementes por Alouatta clamitans (Cabrera, 1940) em um fragmento urbano de mata atlântica da cidade de São Paulo - Benedicto, Denise Manfrin (2015)
For any action in fauna’s conservation it is necessary to have the previous knowledge of the species in order to adopt the best intervention strategies and to optimize the process. This way, even though the Southern Brown Howler monkey is considered vulnerable to extinction in Sao Paulo State, by the Environment Ministry, few studies on these animals have been conducted at the Fontes do Ipiranga State Park - PEFI, Atlantic Forest urban fragment in the city of Sao Paulo. Therefore, this study is aimed to get basic information about the ecology of the two groups that inhabit the region, as home range, activity pattern and diet, create data in the role they play in the maintenance and regeneration of the forest, as the seed dispersers and to analyze the effects on germination in seeds that passes through their digestive tract. The groups were followed in the period of November 2013 to October 2014, the group in the Zoological Park Foundation of São Paulo (area 1), with the final number of five individuals, and the group in the Botanical Garden of São Paulo (area 2), with final composition of nine individuals, both located in the protected area Fontes do Ipiranga State Park - PEFI. The areas belong to different zoning in the management plan of the protected area, and have different degrees of conservation of its forest. Each group was monitored monthly for three full days. Diet items were recorded by the ad libitum method and subsequently identified, totaling 55 species. Syagrus romanzoffiana highlighted by the large participation in the diet of both groups. The seed germination tests comparing a control group (seeds that have not passed through the digestive tract) with samples taken from animal feces showed a significant positive effect on Ficus luschnathiana and Cecropia spp. seeds. The home range was determined by the method of the Minimum Convex Polygons with points being marked in the GPS every half hour, and found home range of 3.5 ha and 5.6 ha for the area’s groups 1 and 2, respectively. The activity pattern was made by the scan sampling method, with scanning every ten minutes and resulted in the usual pattern described for the species: high percentages of time spent resting and low social interaction.